Dual-Role Conflict: Healthcare Provider or Medical Power of Attorney - Nortjé, Maya; Pontarelli, Maureen; Doherty, Ian; Nortjé, Nico (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
This case looks at the tension created when a family member, who is a medical provider, is also the decision-maker for a dying parent.  This case study illustrates the ethics of professional responsibilities and dual-role conflicts.